2nd edition with amendmants to the laws issued in 1995 (Hanoi, 1995)
“Fundamental” (or basic) principles of Vietnamese law are an important concept. For example, while certain contracts with Vietnamese counterparties could be governed by Foreign Law, the choice of foreign law must not be contrary to fundamental principles of Vietnamese law. Vietnamese courts may refuse recognition of foreign arbitration awards if such awards are contrary to fundamental principles of Vietnamese law. Until recently, there is no clear guidance about what fundamental principles of Vietnamese law are. In March 2014, under Resolution 1/2014 implementing the Law on Commercial Arbitration, the Supreme Court seems to be for the first time has given some limited guidance on fundamental principles of Vietnamese law.
Keywords: Luật thương mại,Commercial law; Việt Nam,Vietnam